Financial accounting an introduction - Collins, Jake (States Academic Press, 2022)
Financial accounting is a branch of accounting which focuses on generation of financial statements with an objective of recording, summarizing and reporting the transactions of a business. These statements include cash flow statement, income statement and balance sheet. The Income Statement of a company is its net income for a certain period of time. It is the total revenue of a company minus its total expenses. Balance sheet shows what a company owns and owes in forms of assets and liabilities. A cash flow statement is a detailed document which shows a company's debts and incomes over a specific period of time. These financial statements are often referenced by individuals both inside and outside a company such as management, investors, auditors, suppliers, banks etc. The basic objective of any financial accounting system is to provide a detailed information to the users for rational decision-making and to know the solvency position. This book elucidates the concepts and innovative models around prospective developments with respect to this field. It presents the complex subject of financial accounting in the most comprehensible and easy to understand language. It will provide comprehensive knowledge to the readers.